Minilifting: Short-Scar Rhytidectomy with Thread Lifting - Jung, Kyu Hwa; Lee, Won (Archives of Plastic Surgery, 2024)
Facelifting techniques have been developed over time to mask the aging process. However, conventional facelifts cause scarring. Because of patient demands, various noninvasive lifting techniques have been introduced, including absorbable thread lifting. Minilifting is known for its short-scar excision and is used to improve skin laxity and lifting using absorbable threads but the definition and operation techniques are not certain. In this article, we described the definition, development, and operative techniques used in minilifts. Minilifting procedures represent an added option for patients with minimal scarring and adequate lifting effects.
Keywords: minilifting; thread lifting; PDO lifting